Firm responses to a more generous insurance against high sick pay costs - Caroline King Barnard Hall; Linus Liljeberg; Erica Lindahl (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2022)
This paper presents evidence on how firms react to a more generous insurance against high sick pay costs. We exploit a reform launched in Sweden in 2015, which introduced different thresholds for insurance reimbursement depending on firm size. By comparing workers in smaller firms with workers in large firms over time, we evaluate the effects of the reform. We find no indication of changed behaviour among employees in the smallest firms (on average 15 employees), but an increase in sickness absence among those employed in middle-sized firms (on average 38 employees). The increased absence in middle-sized firms is entirely driven by new hires, but the newly hired employees do not seem to be differently selected. We find no evidence indicating that the more generous insurance made firms more inclined to employ more sick-prone individuals. Further analysis suggests that the absence of behavioural responses among employees in the smallest firms might be related to a large production loss from an absent worker, which the insurance cannot fully compensate for. Taken together, we find no support for any societal benefits of a more generous insurance against high sick pay costs in terms of an increased employment-probability among more sick-prone individuals.
Keywords: J22; J23; L23; M51; 330; sickness absence; sick pay; firm size; insurance; recruitment